2020
DOI: 10.21203/rs.3.rs-131679/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ITGA3 Is a Reliable Biomarker and Putative Therapeutic Target for Glioma

Abstract: Background: Glioma is the most prevalent and malignant primary central nervous system tumor in adults. As a member of the integrin alpha chain family of proteins, integrin subunit alpha 3 (ITGA3) has been found to play a critical role in the occurrence and progression of several cancers, including lung, ovarian, and pancreatic cancers. However, the role of ITGA3 in glioma remains unclear.Methods: The Cancer Genome Atlas (TCGA), Chinese Glioma Genome Atlas (CGGA), REMBRANDT, GSE16011, GSE59612, and GSE4290 data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Recently, BICCN released results of its first implementation phase presenting a multimodal cell census and an atlas of the mammalian primary motor cortex (BICCN, 2021). This massive resource provides a detailed transcriptomic and epigenomic cell atlas of the mouse primary motor cortex (Yao et al, 2021), including its spatial organization (Zhang et al, 2021) and comparison across human, marmoset (a new world monkey) and mouse (Bakken et al, 2021). The integrative analysis of seven scRNA-seq and snRNA-seq datasets led to the identification of 116 cell types, counting 59 classes of inhibitory and 31 classes of excitatory neurons, highlighting their large transcriptional diversity.…”
Section: Oligodendrocyte Heterogeneity In Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, BICCN released results of its first implementation phase presenting a multimodal cell census and an atlas of the mammalian primary motor cortex (BICCN, 2021). This massive resource provides a detailed transcriptomic and epigenomic cell atlas of the mouse primary motor cortex (Yao et al, 2021), including its spatial organization (Zhang et al, 2021) and comparison across human, marmoset (a new world monkey) and mouse (Bakken et al, 2021). The integrative analysis of seven scRNA-seq and snRNA-seq datasets led to the identification of 116 cell types, counting 59 classes of inhibitory and 31 classes of excitatory neurons, highlighting their large transcriptional diversity.…”
Section: Oligodendrocyte Heterogeneity In Healthmentioning
confidence: 99%
“…Through flow cytometry of apoptosis by Annexin V-EGFP/PI double staining, we further confirmed that 35 µM STF083010 could effectively reduce the death of OPCs (Figure 6E), and 0.25 µM GSK2656157 could significantly inhibit the death of OPCs (Figure 6F). Through RNAseq, we found the transcripts of ER stress related genes (Zhang et al, 2021) were significantly up-regulated after SCI (Figures 7A-C). The GO and KEGG pathway analysis also revealed that ER stress associated signaling pathways were activated (Figures 7D, E).…”
Section: Er Stress Inhibition Could Protect Opcs From Death and Inhib...mentioning
confidence: 99%
“…In turn, signal transduction through ER sensors can not only induce UPR but also modulate UPR-independent transcriptional and metabolic pathways, resultantly contributing to tumour initiation, progression, immune evasion, and chemoradiotherapy resistance (Chen and Cubillos-Ruiz, 2021). Prior research has elucidated that ER stress exhibits a significant correlation with the survival outcomes in patients with osteosarcoma (Shi et al, 2022), colon cancer (Liu et al, 2018), renal carcinoma (Zhang et al, 2022), glioma (Zhang et al, 2021). In particular, recent studies show that ER stress can promote stemness and chemoresistance of PC by interfering fatty acid metabolism of tumour cells (Tadros et al, 2017;Dauer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%